Involvement of Sigma Receptor-1 in Lymphatic Endothelial Barrier Integrity and Bioenergetic Regulation - Motawe, Zeinab Y. (Lymphat Res Biol, 2021)
Background: Lymphatic endothelium plays significant roles in lymph transport and maintaining a barrier between the lymph and interstitial compartments. Lymphatic endothelial dysfunction is suspected to be a key factor in the pathogenesis of lymphatic diseases such as lymphedema. Sigma receptor-1 (σ1) was recently identified to promote endothelial-dependent production of nitric oxide and relaxation of collecting lymphatic vessels. In this study, we investigated the potential role of σ1 in lymphatic endothelial barrier function. Methods and Results: Cultured adult human dermal lymphatic endothelial cells (HDLEC) were grown into confluent monolayers. Transendothelial electrical resistance (TER) served as an index of barrier function. Glycolytic rate of HDLEC was determined with the Agilent Seahorse system. The σ1-selective agonist PRE-084 was used to test the impact of σ1 on HDLEC monolayer barrier function and endothelial bioenergetics, whereas the contribution of basal σ1 activity was assessed with small interfering RNA (siRNA)-mediated knockdown of σ1 expression. The ability of σ1 activation to counteract interleukin (IL)-1β-induced barrier dysfunction was also tested. The results show that PRE-084 increases HDLEC TER in a concentration-dependent manner, whereas reducing σ1 expression with siRNA decreases HDLEC TER. PRE-084 also enhances glycolytic rate parameters in HDLEC. Moreover, PRE-084 treatment partially counteracts IL-1β-induced HDLEC monolayer barrier dysfunction. Conclusions: Collectively, the results suggest that σ1 contributes to basal lymphatic endothelial barrier function, potentially through its ability to enhance glycolytic energy production. Our work also highlights the therapeutic potential of σ1 agonists for preventing lymphatic barrier dysfunction caused by inflammatory mediators.